2006
DOI: 10.1016/j.disc.2005.11.029
|View full text |Cite
|
Sign up to set email alerts
|

A survey on labeling graphs with a condition at distance two

Abstract: For positive integers, is the smallest k such that there exists a k-L(d 1 , d 2 )-labeling of G. This class of labelings is motivated by the code (or frequency) assignment problem in computer network. This article surveys the results on this labeling problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
108
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 203 publications
(109 citation statements)
references
References 39 publications
1
108
0
Order By: Relevance
“…In this context, L(2, 1)-labeling is generalized into L(p, q)-labeling for arbitrary nonnegative integers p and q, and in fact, we can see that L(1, 0)-labeling (L(p, 0)-labeling, actually) is equivalent to the classical vertex coloring. We can find a lot of related results on L(p, q)-labelings in comprehensive surveys by Calamoneri [11,12] and by Yeh [68]. The survey paper [12] is still updated and we can download the latest version from a web page 1 .…”
Section: (G) a K-l(p Q)-labeling Is An L(p Q)-labeling F : V (G) →mentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, L(2, 1)-labeling is generalized into L(p, q)-labeling for arbitrary nonnegative integers p and q, and in fact, we can see that L(1, 0)-labeling (L(p, 0)-labeling, actually) is equivalent to the classical vertex coloring. We can find a lot of related results on L(p, q)-labelings in comprehensive surveys by Calamoneri [11,12] and by Yeh [68]. The survey paper [12] is still updated and we can download the latest version from a web page 1 .…”
Section: (G) a K-l(p Q)-labeling Is An L(p Q)-labeling F : V (G) →mentioning
confidence: 99%
“…Then, Griggs and Yeh formally introduced the notion of L(p, q)-labeling in [31,67]. Due to its practical importance, the L(2, 1)-labeling problem has been widely studied.…”
Section: (G) a K-l(p Q)-labeling Is An L(p Q)-labeling F : V (G) →mentioning
confidence: 99%
“…the difference between the largest and the smallest color used. For instance, it was shown that the L( p, q)-labeling problem is NP-complete even for bipartite planar graphs with degree Δ ≤ 4 (Janczewski et al 2009) and polynomially solvable for trees in the case q = 1 (Yeh 2006) and for many simple graph classes: paths, cycles etc. It was also shown that the L(2, 1)-labeling problem is polynomially solvable for cacti (Jonas 1993) and p-almost trees (Fiala and Kratochvil 2001) for every fixed p. Herein we focus on similar minimization criterion: the edge span.…”
Section: Definition 1 Let G = (Vmentioning
confidence: 99%
“…Calamoneri (2006); Yeh (2006) for a survey of results) the authors study the problem of finding colorings with minimal span, i.e. the difference between the largest and the smallest color used.…”
Section: Definition 1 Let G = (Vmentioning
confidence: 99%
“…This problem was introduced by Grrigs and Yeh [12,13] in connection with the problem of assigning frequencies in a multihop radio network. Some results of -labelling problem are given below.…”
mentioning
confidence: 99%